Весільна комора у контексті обрядів господарської магії - Костенко, Л. (Народна творчість та етнографія, 2007)
On basis of rich field material the author of the article investigates the ritual of ‘komora’ (Ukrainian wedding ritual) in various regions, which marks wedding rituals. Till now the household aspect of the ritual was poorly investigated. This aspect is connected with the idea that married couple has influence on fertility of plants and cattle. To investigate this aspect the author of the article used categories ‘chesna moloda’ (chaste bride) and ‘nechesna moloda’ (unchaste bride).